Artificial nacre-like papers based on noncovalent functionalized boron nitride nanosheets with excellent mechanical and thermally conductive properties1. Issue 15 (21st April 2015) - Zeng, Xiaoliang; Ye, Lei; Yu, Shuhui; Li, Hao; Sun, Rong; Xu, Jianbin; Wong, Ching-Ping
<x xml:space="preserve">Abstract</x> Artificial nacre-like papers with excellent mechanical and thermally conductive properties were fabricated via self-assembly of functionalized boron nitride nanosheets and poly(vinyl alcohol).